PENGARUH PENDIDIKAN KARAKTER KEPANDUAN HIZBUL WATHON TERHADAP PRESTASI BELAJAR SISWA DI SMP MUHAMMADIYAH 7 YOGYAKARTA - Heri Kurnia; Fitriyani Khusna Widayanti (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
Based on the results of simple regression analysis with summary models obtained R = 0.608 or rh = 0.608. It aims to find out the hypothesis rejected or accepted with N = 40 while rt = 0.312 then obtained 0.608 ,3 0.312 from these results it can be concluded that Hα is accepted. So it can be concluded that there is an influence between Hizbul Wathon's Scout Character Education with learning achievement. Regression equation, obtained from the determinant coefficient value R ² = 0.370 with the meaning that the character education of Hizbul Wathan contributed to the learning achievement of 37%. So it can be concluded that learning achievement is influenced by Hizbul Wathan's Character Education by 37% while the remaining 63% is influenced by factors outside this study. The simple regression analysis test results obtained by the regression equation: Y = 46.257 + 0.459 X. Based on the simple regression equation can be obtained a constant (α) of 46.257 with the understanding that if the Character Education Hizbul Wathan (X) or equal to zero (0) then the level of achievement learning (Y) of 46,257 units, the variable Hizbul Wathan Character Education (X) obtained a coefficient value of 0.459 which means that if the value of Hizbul Wathan Character Education (X) increases by one unit then the learning achievement (Y) will increase by 0.459 units. Hypothesis testing is done through testing the significance of the regression coefficient of Hizbul Wathan's Character Education variable. With the hypothesis of Hizbul Wathan's Character Education influencing student achievement. The analysis shows that the regression coefficient is 0.459 with a significance level of α = 5%, then the regression coefficient is significant because ρ = 0,000> 0.05.